Хронічний гепатит С зі змішаною кріоглобулінемією: сучасні підходи до лікування - Рябоконь, Юрій Юрійович; Riabokon, Yu. Yu. (ТДМУ, 2016)
Висвітлено проблемні питання лікування хворих на ХГС зі змішаною кріоглобулінемією. Показано, що ерадикація вірусу гепатиту С є головною метою в лікуванні хворих на ХГС зі змішаною кріоглобулінемією. При тяжких формах HCVасоційованого кріоглобулінемічного васкуліту доцільно враховувати можливості патогенетичного лікування. Problematic issues of treatment of patients with chronic hepatitis C with mixed cryoglobulinemia are presented. It is shown that the eradication of virus hepatitis C is a main aim in treatment of patients with chronic hepatitis C with mixed cryoglobulinemia. At severe forms of the HCVassociated cryoglobulinema vasculitis it is expedient to consider possibilities of pathogenetic treatment.
Chronic hepatitis c with mixed cryoglobulinemia: modern approaches to treatment
Keywords: хронічний гепатит С; змішана кріоглобулінемія; лікування; chronic hepatitis C; mixed cryoglobulinemia; treatment